Analysis of the effectiveness of the defensive and offensive performance of the Danish h andball team in the World Handball Championship in Egypt in 2021 - نغال نغال محمد (sports creativity, 2025)
n this study, we aim to analyze the effectiveness of the defensive and offensive performance of handball players by studying the performance of the Danish national team in the world Handball Championship in Egypt in 2021. Where we analyzed the team’s matches and studied them in terms of the types of attacks, the defensive areas and the shooting areas, and their relationship with the defensive and offensive performance. Wefound statistical differences based on the variety of attacks. We also recorded the effectiveness of offensive performance by changing the shootingareas. While we didn’t record any statistical differences according to the different defensive areas except for the central focal area which had an impact on the effectiveness of the players’ defensive performance